2009
DOI: 10.1007/s10493-009-9252-4
|View full text |Cite
|
Sign up to set email alerts
|

The presence of webbing affects the oviposition rate of two-spotted spider mites, Tetranychus urticae (Acari: Tetranychidae)

Abstract: Several species of tetranychid mites including Tetranychus urticae Koch (Acari: Tetranychidae) construct complicated three-dimensional webs on plant leaves. These webs provide protection against biotic and abiotic stress. As producing web is likely to entail a cost, mites that arrive on a leaf with web are expected to refrain from producing it, because they will gain the benefit of protection from the existing web. Mites that produce less web may then allocate resources that are not spent on web construction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
(24 reference statements)
0
13
1
2
Order By: Relevance
“…Com relação aos aspectos reprodutivos, foi observado período de pré-oviposição, oviposição e pós-oviposição de 1,39, 15 e 1,16 dias, respectivamente, com produção média de 59 ovos por fêmea (Tabela 3). Os machos alcançaram longevidade de 23 dias, superior à das fêmeas, o que pode ser explicado pelo maior gasto energético destas com a produção de ovos (Oku et al, 2009 (Rivero & Vásquez, 2009). Silva et al (2009), em estudo com fêmeas de T. urticae em gérbera, relataram valores médios de 3,75 ovos por fêmea por dia, próximos aos encontrados no presente trabalho.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Com relação aos aspectos reprodutivos, foi observado período de pré-oviposição, oviposição e pós-oviposição de 1,39, 15 e 1,16 dias, respectivamente, com produção média de 59 ovos por fêmea (Tabela 3). Os machos alcançaram longevidade de 23 dias, superior à das fêmeas, o que pode ser explicado pelo maior gasto energético destas com a produção de ovos (Oku et al, 2009 (Rivero & Vásquez, 2009). Silva et al (2009), em estudo com fêmeas de T. urticae em gérbera, relataram valores médios de 3,75 ovos por fêmea por dia, próximos aos encontrados no presente trabalho.…”
Section: Resultsunclassified
“…De acordo com Oku et al (2009), espécies da família Tetranychidae produzem menor quantidade de teia quando têm maior disponibilidade de recursos para aumentar outras aptidões, como número de ovos produzidos. Portanto, a alta taxa de oviposição obtida para T. bastosi no presente trabalho -quando comparada à de outras espécies do mesmo gênero -, além de ser uma característica inerente à espécie e a sua adaptação ecológica à disponibilidade de recursos no ambiente, pode consistir, também, numa estratégia de compensação à maior vulnerabilidade a predadores decorrente da menor quantidade de teia produzida.…”
Section: Resultsunclassified
“…Because the feeding modes of the two related spider mite species were identical, fine-scale resource partitioning between individuals living in close proximity (e.g., Daugherty 2009) seems unlikely. Oku et al (2009) demonstrated a web-building cost for T. urticae adult females in terms of reduced egg production during the initial 24 h of web building. Therefore, females introduced secondarily may have offset the costs of possible indirect competition with initial females by reducing web-building costs, that is, by sharing established webs.…”
Section: Discussionmentioning
confidence: 98%
“…We hypothesise that lying down with protective setae represents an alternative antipredator defence for spider mites to producing protective webs. That is, P. citri does not have to produce protective webs that are costly in terms of reduced fecundity (Oku et al 2009), and mites that produce protective webs do not have to lie down most of the time or possess long setae that might be a hindrance when living under a protective web.…”
Section: Discussionmentioning
confidence: 99%